Contact modeling with a finite element model in piston ring‒liner conjunction under dry conditions. Issue 3 (17th July 2019) - Nikolakopoulos, Pantelis G.; Grigoriadis, Kyriakos; Zavos, Anastasios
Abstract : Purpose: The purpose of this paper is to focus on the creation of an isothermal elastic ring-liner model to highlight, through stresses, the occurrence of the plastic deformation in certain crank angles under extreme dry lubrication conditions. Design/methodology/approach: The stresses that are exported from this analysis are pointing out not only the necessity for an elastoplastic model to be created, but also the importance of predicting the correct friction coefficient, as pointed out by both the contact surface stress and that in depth of the two bodies in contact. Findings: The comparison between the finite element model and the adhesion mathematical model of Johnson, Kendall and Roberts seals the importance to calculate the interaction forces, acting on the common solid surface, in the pursuit of defining a propriate contact patch. Additionally, a three-dimensional ring model is built, highlighting the importance of the modeling surface's micro asperities for a solid stress analysis. Also, numerical experiments are conducted, in contact with the cylinder and a piston ring made of an iron alloy and of two different plating materials, such us Chromium (Cr) and Chromium‒Nickel Alloy (CrN). The ability to calculate the stress concentration factor is also described. Originality/value: A three-dimensional ring model is built, highlighting the importance of the modeling surface's micro asperities for a solid stress analysis. Also, numerical experiments are conducted, in contact with the cylinder and a piston ring made of an iron alloy and of two different plating materials, such us Chromium (Cr) and Chromium‒Nickel Alloy (CrN). The ability to calculate the stress concentration factor is also described.